Expression of Ferroptosis-Related Proteins Glutathione Peroxidase 4, Nuclear Factor Erythroid 2-Related Factor 2, and Solute Carrier Family 7 Member 11 in Gastric Cancer Patients - Sun, Yitian; Zhu, Zhiyu; Duan, Ting; Li, Guoxiong (Turkish Journal of Gastroenterology, 2023)
Background/Aims: The aim of this study was to investigate the expression of ferroptosis-related targets glutathione peroxidase 4, nuclear factor erythroid 2-related factor 2, and solute carrier family 7 member 11 in gastric cancer and the correlation between their expression and the clinicopathological characteristics and prognosis of gastric cancer patients. Materials and Methods: Forty-two gastric cancer samples and paracancerous samples were included, and all cases were detected with glutathione peroxidase 4, nuclear factor erythroid 2-related factor 2, and solute carrier family 7 member 11 by immunohistochemistry. Six gastric cancer cell lines and 1 normal gastric epithelial cell were stably cultured, and the expression of target genes of different cell lines was detected using western blot and polymerase chain reaction. Public data were downloaded from the database, and analyses were performed by software including Statistical Package for the Social Sciences and Prism. Results: A high glutathione peroxidase 4 expression level was found in 7 (16.67%) cancer tissues and 0 (0.00%) paracancerous tissues (P = .012). Nuclear factor erythroid 2-related factor 2 was upregulated in 23 (54.76%) cancer tissues and 2 (4.76%) paracancerous tissues (P < .001). Solute carrier family 7 member 11 showed increased expression in 4 (9.52%) cancer tissues and 1 (2.38%) paracancerous tissue (P = .356). No significant association existed between their expression and the clinicopathological characteristics and prognosis of gastric cancer patients. Glutathione peroxidase 4 and nuclear factor erythroid 2-related factor 2 expressions were higher in all 6 gastric cancer cell lines compared to normal gastric epithelial cells. Conclusion: Glutathione peroxidase 4 and nuclear factor erythroid 2-related factor 2 expressions were significantly higher in gastric cancer, which may be potential biomarkers of gastric cancer.